2004
DOI: 10.1021/om0342964
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Ortho-Mercuriated and Ortho-Palladated Arylacetals and Cyclic and Acyclic Aryldithioacetals. New Examples of the Rearrangement of Acyclic Dithioacetal Aryl- to Dithioether Alkyl-Palladium Complexes

Abstract: The arylmercurial [Hg{C6H3(CHO)2-2,5}Cl] (1) reacts with CH(OMe)3 or HS(CH2)2SH to give [Hg{C6H3{CH(OMe)2}2-2,5}Cl] (2) or [Hg(Ara)Cl] [Ara = C6H3{CH(SCH2CH2S)}2-2,5 (3a)], respectively. The mercurial 2 or 3a reacts with (NMe4)2[Pd2Cl6] and 2,2‘-bipyridine (bpy) or with trans-[PdCl2(PPh3)2] to give the aryl-palladium complex [Pd{C6H3{CH(OMe)2}2-2,5}Cl(bpy)] (4) or [Pd(κ2-C,S-Ara)Cl(PPh3)] (5a*), respectively. The reaction of 1 with NaI3 renders IC6H3(CHO)2-2,5 (6), which reacts with HS(CH2)2SH to give IAra (7a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…We report also a systematic study of the reactions of these aryl complexes with CO and XyNC (Xy = 2,6-dimethylphenyl). This type of reactions have been widely studied, as they are involved in the synthesis of acyl [10][11][12][13][14][15] and iminoacyl 11,[13][14][15][16][17][18][19][20] palladium complexes and also in many stoichiometric and catalytic syntheses of organic compounds. [13][14][15][20][21][22] We report in this work that, depending on the substituents on the amidic nitrogen, these insertion reactions lead to isoquinoline-or isocoumarin-based heterocycles resulting from intramolecular C-N or C-O couplings.…”
Section: Introductionmentioning
confidence: 99%
“…We report also a systematic study of the reactions of these aryl complexes with CO and XyNC (Xy = 2,6-dimethylphenyl). This type of reactions have been widely studied, as they are involved in the synthesis of acyl [10][11][12][13][14][15] and iminoacyl 11,[13][14][15][16][17][18][19][20] palladium complexes and also in many stoichiometric and catalytic syntheses of organic compounds. [13][14][15][20][21][22] We report in this work that, depending on the substituents on the amidic nitrogen, these insertion reactions lead to isoquinoline-or isocoumarin-based heterocycles resulting from intramolecular C-N or C-O couplings.…”
Section: Introductionmentioning
confidence: 99%
“…Mass spectra were obtained in a QUATRO mass spectrometer with Cs ion-gun and 3-NBA matrix. NMR spectra were obtained as CDCl 3 solutions and referenced to SiMe 4 ( 1 H, 13 (1) and [Pd{5-(COH)C 6 H 3 -C(H)@NCy-C2,N}(l-Cl)] 2 (2) has been reported previously from this laboratory [17,18]. The phosphine (oTol) 2 P(CH 2 ) 2 P(o-Tol) 2 was prepared as described previously in the literature [61].…”
Section: General Remarksmentioning
confidence: 99%
“…In particular, cyclometallation of Schiff-base ligands with a wide range of transition metals has been extensively investigated. Tetradentate [C,N,C,N] Schiff bases generally undergo double metallation to give compounds with two metal atoms per organic ligand [6][7][8][9][10][11][12][13][14][15][16], however, as we have reported previously, in the case of the potentialy tetradentate ligands derived from isophthalaldehyde, 1,3-(CyN@CH) 2 C 6 H 4 , and terephthalaldehyde, 1,4-(CyN@CH) 2 conditions [17][18][19]. Thus, treatment with palladium(II) acetate in acetic acid gave the monocyclometallated complexes 1 and 2 after cleavage of one C@N double bond, and we have studied the reactivity of these cyclometallated complexes towards different mono and bidentate ligands [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of the nature of these fluxional processes is useful in understanding the dynamics of this type of ligand and the development of new hemilabile ligand sets for use in homogeneous catalysis [6]. During the course of this work Vicente et al reported the preparation of some analogous orthomercuriated arylacetals and their utility as transfer reagents in the preparation of some orthopalladated arylacetal complexes [7]. The number of other examples of cyclometallated (g 2 -C,O coordinated) aryl acetals is limited [8].…”
Section: Introductionmentioning
confidence: 99%
“…For related thioether-containing complexes pyramidal geometry at sulfur is, as expected, normal. For example Vicente et al have recently reported the solid state structure of the cyclopalladated thioacetal-containing complex [PdCl{g 2 -C,S-C 6 H 3 -2,5-(CHS 2 C 2 H 4 )}(PPh 3 )] and the thioacetal ligand is pyramidal at sulfur [7].…”
Section: Introductionmentioning
confidence: 99%